Impact of polysaccharides and lecithin as fat replacers on quality of low fat UF soft cheese - Ibrahim, Eman M (Indian Journal of Dairy Science, 2018)
The aim of this study was to evaluate the effects of incorporating polysaccharides (xanthan, sodium carboxymethylcellulose and EPS producing culture) and lecithin in low-fat UF soft cheese on the physicochemical, rheological and sensory properties of cheese.Low- fat milk.retentate used was divided into five equal portions. The first one with no additives was served as a control (LFC). The rest portions were supplemented with xanthan (0.005%, XAN), sodium carboxymethylcellulose (0.1%, CMC), EPS-producing cultures (0.02%, EPS) andlecithin (0.2%, LEC), respectively and standardized fat milk retentate (15% fat) without additives was used as positive control (FFC) . The main results showed that moisture content of low fat UF-soft cheeses made with EPS-producing starter culture and lecithin were significantly higher than those cheese samples without additives. EPS treatment showed that the highest value of acidity, SN/TN and TVFA, and the lowest value of Fat content. Rheological properties decreased significantly like Hardness, adhesiveness, springiness, gumminess, and chewiness and the maximum decrease was for treatment of EPS.Evaluation of organoleptic properties showed that treatment of EPS had the highest score while control (LFE) had the lowest score in this respect.